2015
DOI: 10.1002/icd.1924
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parent Education and Parenting Knowledge in Children's Language and Literacy Skills among White, Black, and Latino Families

Abstract: This study investigated the role of parenting knowledge of infant development in children's subsequent language and pre-literacy skills among White, Black and Latino families of varying socioeconomic status. Data come from 6,150 participants in the Early Childhood Longitudinal Study-Birth Cohort. Mothers' knowledge of infant development was measured when children were 9 months old, and child language and pre-literacy skills were measured during the fall of the preschool year prior to Kindergarten when children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 50 publications
(71 reference statements)
12
88
0
6
Order By: Relevance
“…A total KIDI score was calculated by summing points for correct answers. The reliability of KIDI scores was .63 in the final sample in this study, which is fairly comparable with that reported in the KIDI standardization manual (see Bornstein et al, 2010;Rowe et al, 2015). The reliabilities of the KIDI scores and the other variables used in this study were slightly lower than is considered optimal; however, they are consistent with what other researchers using large-scale national datasets have found (e.g., Crosnoe & Cooper, 2010;Sonnenschein & Galindo, 2015).…”
Section: The Present Studysupporting
confidence: 89%
See 1 more Smart Citation
“…A total KIDI score was calculated by summing points for correct answers. The reliability of KIDI scores was .63 in the final sample in this study, which is fairly comparable with that reported in the KIDI standardization manual (see Bornstein et al, 2010;Rowe et al, 2015). The reliabilities of the KIDI scores and the other variables used in this study were slightly lower than is considered optimal; however, they are consistent with what other researchers using large-scale national datasets have found (e.g., Crosnoe & Cooper, 2010;Sonnenschein & Galindo, 2015).…”
Section: The Present Studysupporting
confidence: 89%
“…We also do not know much about whether parents' knowledge of children's development continues to predict children's development as they enter school. Rowe et al () found that Black, Latino, and White parents' knowledge, assessed when children were 9 months old, predicted children's early language and literacy scores when children were in preschool. Parents' knowledge mediated the relation between maternal education and children's outcomes.…”
Section: Parents' Knowledge Of Children's Developmentmentioning
confidence: 99%
“…Factors of socioeconomic status (SES), parent educational levels, race and ethnicity, sources of parent knowledge and access to services have been recognized as contributing to parent knowledge and practices [15, 16]. Rowe et al [16] study supported previous studies and showed a link between parent knowledge and parent communication practices, regarding language and literacy in young children. They concluded that the gaps in language and literacy skills identified in preschool could be explained as relating to the levels of early parental knowledge on child development.…”
Section: Role Of Parents In Children’s Language and Literacy Learningsupporting
confidence: 77%
“…The role of parent knowledge and practices relating to child language and literacy skills has been explored extensively in the literature [15, 16]. Factors of socioeconomic status (SES), parent educational levels, race and ethnicity, sources of parent knowledge and access to services have been recognized as contributing to parent knowledge and practices [15, 16].…”
Section: Role Of Parents In Children’s Language and Literacy Learningmentioning
confidence: 99%
“…Indeed, in one study , some of the relation between parents’ education and parenting knowledge was because of parents’ access to written materials. In another study, parents’ years of education were related significantly to whether they reported turning to professionals (e.g., doctors, nurses, child care providers) rather than family members for help with parenting and information about parenting .…”
Section: Parents’ Input and Other Factorsmentioning
confidence: 98%